Пошаговое объяснение:
1) 1,9 + (-4,2) + 5,9 + (-4,7) + 2,7 =
1,9 - 4,2 + 5,9 - 4,7 + 2,7 = 1,6
Противоположное число = -1,6
2) -1,9 + 4,2 + (-5,9) + 4,7 + (-2,7) =
-1,9 + 4,2 - 5,9 + 4,7 - 2,7 = -1,6
3) 1,9 + 4,2 + 5,9 + 4,7 + 2,7 = 19,4
1. 1,9+(-4,2)+5,9+(-4,7)+2,7=1,9-4,2+5,9-4,7+2,7=1,6
протилежне число -1,6
2. -1,9+4,2+(-5,9)+4,7+(-2,7)=-1,9+4,2-5,9+4,7-2,7=-1,6
3.1,9+4,2+5,9+4,7+2,7=19,4
Пошаговое объяснение:
1) 1,9 + (-4,2) + 5,9 + (-4,7) + 2,7 =
1,9 - 4,2 + 5,9 - 4,7 + 2,7 = 1,6
Противоположное число = -1,6
2) -1,9 + 4,2 + (-5,9) + 4,7 + (-2,7) =
-1,9 + 4,2 - 5,9 + 4,7 - 2,7 = -1,6
3) 1,9 + 4,2 + 5,9 + 4,7 + 2,7 = 19,4
Пошаговое объяснение:
1. 1,9+(-4,2)+5,9+(-4,7)+2,7=1,9-4,2+5,9-4,7+2,7=1,6
протилежне число -1,6
2. -1,9+4,2+(-5,9)+4,7+(-2,7)=-1,9+4,2-5,9+4,7-2,7=-1,6
3.1,9+4,2+5,9+4,7+2,7=19,4